Local studies provide a global perspective of the impacts of climate change on Indigenous Peoples and local communities - Reyes‑García, V.; García‑Del‑Amo, D.; Porcuna‑Ferrer, A.; Schlingmann, A.; Abazeri, M.; Attoh, Emmanuel M. N. A. N.; Ávila, J. V. d. C.; Ayanlade, A.; Babai, D.; Benyei, P.; Calvet‑Mir, L.; Carmona, R.; et al. (Springer, 2024)
Indigenous Peoples and local communities with nature-dependent livelihoods are disproportionately affected by climate change impacts, but their experience, knowledge and needs receive inadequate attention in climate research and policy. Here, we discuss three key findings of a collaborative research consortium arising from the Local Indicators of Climate Change Impacts project. First, reports of environmental change by Indigenous Peoples and local communities provide holistic, relational, placed-based, culturally-grounded and multi-causal understandings of change, largely focused on processes and elements that are relevant to local livelihoods and cultures. These reports demonstrate that the impacts of climate change intersect with and exacerbate historical effects of socioeconomic and political marginalization. Second, drawing on rich bodies of inter-generational knowledge, Indigenous Peoples and local communities have developed context-specific responses to environmental change grounded in local resources and strategies that often absorb the impacts of multiple drivers of change. Indigenous Peoples and local communities adjust in diverse ways to impacts on their livelihoods, but the adoption of responses often comes at a significant cost due to economic, political, and socio-cultural barriers operating at societal, community, household, and individual levels. Finally, divergent understandings of change challenge generalizations in research examining the human dimensions of climate change. Evidence from Indigenous and local knowledge systems is context-dependent and not always aligned with scientific evidence. Exploring divergent understandings of the concept of change derived from different knowledge systems can yield new insights which may help prioritize research and policy actions to address local needs and priorities.